The Effect of Word Mapping Technique on Students’ Vocabulary Mastery at the Eighth Grade of SMPT Mulia Hati Insani Warunggunung - Anang Jamaludin; Masrupi Masrupi; Raswadi Raswadi; Iim Khairunnisa; Eneng Liah Khoiriyah; Eka Dewi Fithrotunnisa; Dede Imtihanudin (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
The purpose of this study was to examine the effect of word mapping technique on vocabulary acquisition of 8th grade students of SMPT Mulia Hati Insani Warungunung. The quantitative research method was conducted using a pseudo-experimental design. The sample of this study amounted to 62 students who were divided into experimental and control classes. Tests were used to collect data on students' vocabulary acquisition scores, and t-test was used to analyze the data. For the experimental class, the average post-test score was (75.35), higher than the pre-test score (34.81). From the independent sample t-test analysis, the value of t count (11.096) > t table (1.671) was obtained. It’s mean Ho is rejected and Ha is accepted. The effect size value of 2.814 indicates a very large influence. In conclusion, there is a significant effect on speaking ability between students who are taught using the word mapping method and those who are not taught using the word mapping method.